PREVALENSI CACING SALURAN PENCERNAAN PADA SAPI BALI DI KECAMATAN CANDIPURO KABUPATEN LAMPUNG SELATAN - M. Elvin Ramadhan, Madi Hartono, Sri Suharyati, dan Purnama Edy Santosa (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2018)
The research held on Candipuro Districk South Lampung Regency in December 2017--January 2018. This research was to know prevalence of gastrointestinal helminths on Balinese cattle. The research used survey method. Data collection was done by taking all faecal samples from 80 balinese cattles at 6 villages in Candipuro District. Faecal samples examination checked with Mc. Master and Sendimentation test at Veterinary Laboratory. Data was analyzed by descriptively. In result indicated that prevalence of gastrointestinal helminths balinese cattle at Candipuro District South Lampung Regency about 51,25%. The highest prevalence found in Batu Liman village about 82,35% and the lowest prevalence found in Beringin Kencana village about 33,33%. Helmiths species that found in balinese cattle at Candipuro District South Lampung Regency are from Nematode class (Haemanchus sp., Oesophagustomum sp., dan Strongyloides sp.), Trematode class (Paramphistomum sp.) and Cestode class (Moniezia sp.). Keywords: Gastrointestinal helminths, Prevalence, Balinese cattle.